2006
DOI: 10.1117/12.646858
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of GaN epitaxial films grown on SiN x and TiN x porous network templates

Abstract: We report on the structural, electrical, and optical characterization of GaN epitaxial layers grown by metalorganic chemical vapor deposition (MOCVD) on SiN x and TiN x porous templates in order to reduce the density of extended defects. Observations by transmission electron microscopy (TEM) indicate an order of magnitude reduction in the dislocation density in GaN layers grown on TiN x and SiN x networks (down to ~10 8 cm -2 ) compared with the control GaN layers. Both SiN x and TiN x porous network structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…Naturally, nanoscale porous TiN structures have been reported to be prone to delamination due to their lower adhesion surface area compared to compact and layered TiN structures. 38,51 However, this study confirmed that the porous TiN structure remained firmly bonded to the substrate without delamination (Figure 2b), enabling the porous structure to be more effective at releasing the accumulated residual stress. Cross-section images of TiN formation on the sapphire substrate verified the claim that the porous TiN structure showed little defects caused by delamination, unlike the compact TiN layer (Figure S3).…”
Section: Theoretical and Empirical Validations Of The Gansupporting
confidence: 52%
See 4 more Smart Citations
“…Naturally, nanoscale porous TiN structures have been reported to be prone to delamination due to their lower adhesion surface area compared to compact and layered TiN structures. 38,51 However, this study confirmed that the porous TiN structure remained firmly bonded to the substrate without delamination (Figure 2b), enabling the porous structure to be more effective at releasing the accumulated residual stress. Cross-section images of TiN formation on the sapphire substrate verified the claim that the porous TiN structure showed little defects caused by delamination, unlike the compact TiN layer (Figure S3).…”
Section: Theoretical and Empirical Validations Of The Gansupporting
confidence: 52%
“…This preliminary study revealed that most parts of the GaN/TiN epitaxy grown on foreign sapphire were destroyed after the delamination tests. Although the TiN buffer layer are well known to successfully reduce the lattice mismatch of the heteroepitaxy system, the low wettability of TiN with the nucleation site of the GaN may hinder the formation of a mechanically compatible structure due to the interfacial defects. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations